Development of Vertebrates Diversity Booklet at Siantar Zoo as a Learning Resource on Biodiversity Topic - Saragih, Asnawi (Universitas Sulawesi Barat, 2024)
The lack of learning resources results in a less than optimal learning experience which also causes less than optimal learning outcomes. Thus, research on the development of booklet as learning resource needs to be carried out to assist teachers and facilitating learning and assisting students in understanding the material. This study aims to develop vertebrate diversity booklet at Siantar Zoo as a leaning resource on biodiversity topic grade X SMA N 1 Pematangsiantar. This research method is a Research and Development (R&D) study, adapted form Thiagarajan’s 4D (Define, Design, Development, and Disseminate) model. As for the booklet to obtain feasibility and effectiveness, a validity test based on material and media experts and an effectiveness test is used, which is then analyzed with descriptive analysis. The booklet was tested for feasibility by material experts (88%), and media experts (87.5%) with a very feasible category, and teacher responses (94%) and students (95.21 %) with a very feasible category. The independent samples t-test shows that the significance value is 0.000 <0.05. which shows that there is a difference in learning outcomes between the experimental class and the control class. The vertebrate diversity booklet at Siantar Zoo is quite effective as a learning resource with an average score of N-Gain of 0.625 with moderate criteria.